A Comparison Between Rome III and Rome IV Criteria in Children with Chronic Abdominal Pain: A Prospective Observational Cohort Study - Demirören, Kaan; Güney, Bünyamin; Bostancı, Muharrem; Ekici, Deniz (Turkish Journal of Gastroenterology, 2022)
Background: The Rome IV includes a redefinition of functional gastrointestinal disorders and diagnostic criteria. The present study aimed to compare the Rome III and Rome IV classification results and to reveal their differences in children with chronic abdominal pain. Methods: The present study is a prospective observational cohort study. Three hundred forty-four children, who were admitted to the pediatric gastroenterology clinic, had abdominal pain for more than 2 months, and were not diagnosed with an organic disease, were included in our study. Results: In children with chronic abdominal pain, Rome IV criteria did not cause a change in the number of patients diagnosed with functional abdominal pain disorders according to Rome III (89.8% vs 89.2%, P >.05). Functional abdominal pain and functional abdominal pain syndrome were the most common diagnoses in Rome III and functional abdominal pain, not otherwise specified in Rome IV. When compared to Rome III, while the diagnosis of functional dyspepsia increased in Rome IV, irritable bowel syndrome decreased. Conclusion: In children with chronic abdominal pain, Rome IV criteria did not cause a change in the number of patients diagnosed with functional abdominal pain disorders according to Rome III, but it caused a diagnostic shift. It was seen that some of the children diagnosed with irritable bowel syndrome in Rome III shifted to functional dyspepsia diagnosis in Rome IV Cite this article as: Demirören K, Güney B, Bostancı M, Ekici D. A comparison between Rome III and Rome IV criteria in children with chronic abdominal pain: A prospective observational cohort study. Turk J Gastroenterol. 2022;33(11):979-984.